Intrinsic and Extrinsic Properties Affecting Innate Immune Responses to Nanoparticles: The Case of Cerium Oxide - Casals, Eudald; Gusta, Muriel F.; Piella, Jordi; Casals, Gregori; Jiménez, Wladimiro; Puntes, Victor (Frontiers in Immunology, 2017)
We review the apparent discrepancies between studies that report anti-inflammatory effects of cerium oxide nanoparticles (CeO2 NPs) through their reactive oxygen species-chelating properties and immunological studies highlighting their toxicity. We observe that several underappreciated parameters, such as aggregation size and degree of impurity, are critical determinants that need to be carefully addressed to better understand the nanoparticle biological effects in order to unleash their potential clinical benefits. This is because NPs can evolve towards different states, depending on the environment where they have been dispersed and how they have been dispersed. As a consequence, final characteristics of NPs can be very different from what was initially designed and produced in the laboratory. Thus, aggregation, corrosion, and interaction with extracellular matrix proteins critically modify NP features and fate. These modifications depend to a large extent on the characteristics of the biological media in which the NPs are dispersed. As aconsequence, when reviewing the scientific literature, it seems that the aggregation state of NPs, which depends on the characteristics of the dispersing media, may be more significant than the composition or original size of the NPs. In this work, we focus on CeO2 NPs, which are reported sometimes to be protective and anti-inflammatory, and sometimes toxic and pro-inflammatory.